KEEFEKTIFAN EKSTRAK DAUN Carica papaya Linn. DENGAN METODE RACUN LAMBUNG UNTUK PENGENDALIAN RAYAP TANAH Coptotermes sp. (Isoptera: Rhinotermitidae) - Zulyusri, Zulyusri; Desyanti, Desyanti; Ramadani, Rosi Fitri (IAIN Batusangkar, 2012)
Termite Coptotermes sp. is one of the most harmful types of termite class of Rhinotermitidae, Coptotermes genus. One of the controlling efforts is by using an extract of Carica papaya leaves. This study aims at finding out the effectiveness of the leaf extract Carica papaya on the termite Coptotermes sp. Mortality, as well as finding out the concentration of the extract of papaya C. leaf highly effecting on controlling the termites Coptotermes sp. This was an experimental research with Completely Randomized Sampling (CRS) in six extract treatments (0%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%) and 3 replications. The mortality data and the loss of feed were analyzed through the analysis of variance (ANOVA) and followed by Duncan test at 5% significance level. The lethal concentration (LC) and lethal time (LT) were analyzed by Probit analysis. The results showed that the leaf extract of Carica papaya can be used to control termites and it functions most effectively at a concentration of 1.5%. The lethal concentration (LC) leaf extract of Carica papaya is 0.005 and lethal time (LT) is 3.201 days. Key words: Coptotermes sp., extract of Carica papaya leaves